Trading Halts and Market Activity: An Analysis of Volume at the Open and the Close. - Gerety, Mason S; Mulherin, J Harold (Journal of Finance, 1992)
This paper analyzes how the daily opening and closing of financial markets affect trading volume. The authors model the desire to trade at the beginning and end of the day a a function of overnight return volatility. NYSE data from 1933-88 indicate that closing volume is positively related.to expected overnight volatility, while volume at the open is positively related to both expected and unexpected volatility from the previous night. The authors interpret the symmetric response of trading at the open and the close to expected volatility as being due to investor heterogeneities in the ability to bear risk when the market is closed. This desire of investors to trade prior to market closings indicates a cost of mandating marketwide circuit breakers.